Comparison of the intervertebral disc spaces between axial and anterior lean cervical traction - Chung, Chin-Teng (Springer-Verlag, 2009)
The insufficient investigations on the changes of spinal structures during traction prevent further exploring the possible therapeutic mechanism of cervical traction. A blind randomized crossover-design study was conducted to quantitatively compare the intervertebral disc spaces between axial and anterior lean cervical traction in sitting position. A total of 96 radiographic images from the baseline measurements, axial and anterior lean tractions in 32 asymptomatic subjects were digitized for further analysis. The intra- and inter-examiner reliabilities for measuring the intervertebral disc spaces were in good ranges (ICCs = 0.928–0.942). With the application of anterior lean traction, the statistical increases were detected both in anterior and in posterior disc spaces compared to the baseline (0.29 mm and 0.24 mm; both P < 0.01) and axial traction (0.16 mm and 0.35 mm; both P < 0.01). The greater intervertebral disc spaces obtained during anterior lean traction might be associated with the more even distribution of traction forces over the anterior and posterior neck structures. The neck extension moment through mandible that generally occurred in the axial traction could be counteracted by the downward force of head weight during anterior lean traction. This study quantitatively demonstrated that anterior lean traction in sitting position provided more intervertebral disc space enlargements in both anterior and posterior aspects than axial traction did. These findings may serve as a therapeutic reference when cervical traction is suggested.